(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
Monte Cildá was a settlement of ancient Cantabria. There, we have found an important number of epigraphic monuments (with and without text). Through the study of the monuments with text, we are going to explain the onomastic and the social structure of people that lived in Monte Cildá, focusing on people with duo nomina.